2017
DOI: 10.1186/s12909-017-0941-0
|View full text |Cite
|
Sign up to set email alerts
|

Supervision and autonomy of ophthalmology residents in the outpatient Clinic in the United States: a survey of ACGME-accredited programs

Abstract: BackgroundThe development and demonstration of incremental trainee autonomy is required by the ACGME. However, there is scant published research concerning autonomy of ophthalmology residents in the outpatient clinic setting. This study explored the landscape of resident ophthalmology outpatient clinics in the United States.MethodsA link to an online survey using the QualtricsTM platform was emailed to the program directors of all 115 ACGME-accredited ophthalmology programs in the United States. Survey questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…With the increasing expectations for resident supervision and the decrease in resident work hours, over the last 15 years, the implementation of 24-hour coverage by hospitalists has become more common, resulting in a decrease in resident experience managing patients without direct supervision immediately available; however, this is not uniformly rated by residents as being detrimental to their education [35,36]. Another time-honored practice for promoting resident autonomy is the continuity clinic, which has been (and in many cases continues to be) a common part of training for pediatric [37], internal medicine [38], neurology [39], obstetrics and gynecology [40], and even ophthalmology [41] residencies. Although the level of supervision in continuity clinics varies by institution [41], continuity clinics provide the opportunity for residents to be involved in longitudinal care, develop a strong sense of ownership for their patients, and practice some degree of independent decision making.…”
Section: Traditional Methods Of Granting Autonomymentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing expectations for resident supervision and the decrease in resident work hours, over the last 15 years, the implementation of 24-hour coverage by hospitalists has become more common, resulting in a decrease in resident experience managing patients without direct supervision immediately available; however, this is not uniformly rated by residents as being detrimental to their education [35,36]. Another time-honored practice for promoting resident autonomy is the continuity clinic, which has been (and in many cases continues to be) a common part of training for pediatric [37], internal medicine [38], neurology [39], obstetrics and gynecology [40], and even ophthalmology [41] residencies. Although the level of supervision in continuity clinics varies by institution [41], continuity clinics provide the opportunity for residents to be involved in longitudinal care, develop a strong sense of ownership for their patients, and practice some degree of independent decision making.…”
Section: Traditional Methods Of Granting Autonomymentioning
confidence: 99%
“…Another time-honored practice for promoting resident autonomy is the continuity clinic, which has been (and in many cases continues to be) a common part of training for pediatric [37], internal medicine [38], neurology [39], obstetrics and gynecology [40], and even ophthalmology [41] residencies. Although the level of supervision in continuity clinics varies by institution [41], continuity clinics provide the opportunity for residents to be involved in longitudinal care, develop a strong sense of ownership for their patients, and practice some degree of independent decision making.…”
Section: Traditional Methods Of Granting Autonomymentioning
confidence: 99%
“…Literature from both surgical and medical specialties suggests a gradual decline in resident autonomy over time with ramifications on resident satisfaction and preparedness for future practice. [1][2][3][4][5] Here, we describe the actualization of resident-run autonomy clinics within our programme and compare 2 years of survey data to assess resident perception of autonomy before and after implementation.…”
Section: Impact Of Resident Autonomy Clinics In a Dermatology Residenmentioning
confidence: 99%
“…Balancing autonomy and supervision is both a goal and challenge of graduate medical education [18]. In a previous report, we presented the landscape of supervision styles for ophthalmology trainees in the outpatient clinic setting [2]. That study, based upon a survey of program directors, suggested that there was no substantial correlation between the level of supervision in the outpatient setting and metrics such as the number of residents in the program, demographic sites of the clinics, number of faculty or contributions of resident-hosted clinics to overall resident surgery volumes.…”
Section: Introductionmentioning
confidence: 99%